Russian Federation : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
Propelled by large terms-of-trade gains, GDP growth has accelerated and is running close to potential. The demand pressures associated with the large terms-of-trade gains are reflected in a fast real appreciation of the ruble, although more of this has come through nominal appreciation during the last year. IMF staff welcomed the greater focus on inflation control, but cautioned that additional exchange rate flexibility would be needed to meet the end-2006 target. The authorities agreed that structural reforms are behind.